วาระข่าวสารและทิศทางเนี้อหาเกี่ยวกับนโยบายประชานิยม ที่นำเสนอผ่านหนังสือพิมพ์ในยุครัฐบาลทักษิณและหลังรัฐบาลทักษิณ - นพวงษ์ มังคละชน (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This study aims at studying content about populist policies implemented during the Thaksin Shinawatra administration and the interim administration under Gen Surayud Chullanont in three selected newspapers – Matichon, Thai Rath and Krungthep Thurakit. Content analysis of news and editorials about major populist policies namely – universal healthcare, affordable housing program and legalized lottery policy -- was conducted between 9 February 2001 and 20 September 2007, alongside in-depth interviews with editors and news chiefs at the respective newspapers. The research has these findings. The studied newspapers presented different news agenda and content direction during the Thaksin administration from the Surayud administration. During Thaksin administration, the newspapers put emphasis on policy and progress in policy implementation. Most of the news sources found are from government sector. During the Surayud administration, the newspapers put more emphasis on the policy change and adjustment, as well as anti-corruption policy. Most of the news sources are independent organizations. The 30-baht universal healthcare policy was presented during Thaksin administration as a policy that enabled health care rights of citizens but had problems in terms of management which led to conflict between civil servants and politicians. As for the Surayud government, the news was presented in the direction that pointed to the flaw of budget allocation during the Thaksin administration. As for the legalized lottery policy, it was presented in the selected papers as a policy that helped resolve the problem of power warlords but it led to social problem that received both supports and opposition. During the Surayud government, the same policy was presented as non-transparent and bad for the society. With respect to affordable housing program policy, it was presented during the Thaksin administration as a policy that assisted poor people for a better living while during the Surayud government it was presented as a corrupt and substandard policy that affects the people and the country. All the studied newspapers presented their content differently. Business newspapers stress issues about opinions and reactions of people towards government policy rather than progress in policy implementation as in other newspapers. In all, it could be concluded that news presentation about populist policies are determined by the judgment of journalists, newspapers’ standpoint, social situation, government behavior, processes and steps of populist policy and news values.